Indoor Particulate Matters Measured in Residential Homes in the Southeastern United States: Effects of Pandemic Lockdown and Holiday Cooking - Sierra Laltrello; Azita Amiri; Shan-Hu Lee (Aerosol and Air Quality Research)
Abstract Although humans spend a majority of their lives in indoor environments, indoor air quality is immensely understudied, compared to ambient air. Here, we show the first long-term measurements of household indoor PM concentrations in the southeastern United States, for one year (May 2019 through April 2020) covering the COVID-19 hard-lockdown period (March and April 2020). Particle size distributions between 0.25–35 µm were measured with a low-cost sensor, which does not utilize hazardous chemicals and radiation sources and is ideal for indoor air monitoring in real households without disruption of residents’ living conditions. Our observations show that while cooking and cleaning are two major emissions sources for the residential indoor PM, consistent with the literature knowledge, but we also show that human occupancy affects the indoor PM level substantially. During the hard lockdown during the COVID-19 pandemic, the background level of indoor PM increased by ~200%, while the ambient PM decreased by ~50% during the same period. Before the pandemic, the indoor PM level was lower than the outdoor, but it became similar or higher than the outdoor level during the pandemic. Thanksgiving holiday cooking (prior to COVID-19) produced high concentrations of PM for an extended period (e.g., over 6 hours) even with active kitchen ventilation. PM concentrations during a cooking and cleaning event usually increased linearly to a maximum value and then decayed exponentially. The decay time of indoor PM ranged from several minutes up to ~100 minutes and increased with the particle size, indicating that particle deposition to the interior surfaces is the main sink process of the indoor PM.